PENGARUH MEDIA TEKA-TEKI SILANG TERHADAP HASIL BELAJAR SISWA PADA MUATAN IPS KELAS V SDN 61 KARARA KOTA BIMA TAHUN PELAJARAN 2021/2022 (PIONIR: JURNAL PENDIDIKAN, 2021)
The objectives of this study were (1) To determine the ability of teachers in implementing STAD type cooperative learning in Physics Lessons in class X-MIPA 1, (2) to increase student activity and (3) to improve student learning outcomes in class X-MIPA 1 SMAN 2 Banda Aceh on Physics Lessons in Circular Motion with the application of the STAD type cooperative learning model. The subjects of this study were students of class X-MIPA 1 with a total of 32 students. Data collection techniques in this study were through tests, observations, and questionnaires. Data collection tools used were observation sheets, test questions, and student response questionnaires. Data analysis was carried out by descriptive qualitative. Data processing is done in a way; (a) to see the activities of teachers and students through observation sheets, processed using descriptive statistics with an average score, (b) data on student learning outcomes is processed by looking at the level of individual and classical completeness, (c) the results of the data from the questionnaire are processed using simple percentage formula. The results showed that the teacher's ability to manage learning in the first cycle was declared almost good (3.56) then increased in cycle II with good criteria (4.42), while student activity in the first cycle was good enough (3.19) then the second cycle was good criterion (4.05). Thus the learning process has increased significantly so that it affects student learning outcomes which are quite good, namely student learning outcomes at the beginning of observation of student learning completeness only 53% of 32 students meaning students who did not complete learning as much as 47% , then after being given action with cooperative learning type STAD in the first cycle students who completed learning increased to 68.75%, who had not yet completed it decreased to 32.25% and in the second cycle students who completed learning increased to 81.25% and those who did not complete reduced to 18.75%.
Keywords: Medium Crossword Puzzle; Social Science Learning Outcomes.